2018
DOI: 10.1007/s11356-018-2885-2
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and drinking water quality indicators in Mongolia

Abstract: Mongolia is characterized by restricted sources of drinking water and intensive water pollution due to high rates of urbanization, mining industry development, enormous amount of livestock, and ever-growing attempts in domestic production of cereals and vegetables. Among others, Se is the least studied element in Mongolian water resources. Based on fluorimetric method of analysis, the first results on Se levels in drinking water of five aimags, Ulaanbaatar, and Erdenet were obtained. Uneven distribution of Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These findings could be explained by the fact that selenium can be reached to soils or an aquatic environment through weathering of rocks, aeolian deposition, fluvial input, suspension load and biological effect (El-Badry and Khalifa, 2017). Recently, high levels of selenium are steadily found in groundwater and drinking water around the world (Golubkina et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be explained by the fact that selenium can be reached to soils or an aquatic environment through weathering of rocks, aeolian deposition, fluvial input, suspension load and biological effect (El-Badry and Khalifa, 2017). Recently, high levels of selenium are steadily found in groundwater and drinking water around the world (Golubkina et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…2017 ; Edet et al. 2004 ; Giri and Singh 2015 ; Golubkina et al. 2018 ; Iqbal and Shah 2012 ; Kavanagh et al.…”
Section: Discussionmentioning
confidence: 99%
“…Two metals, As (49:2% ± 37:6%) and Cr (25:5% ± 32:3%), were significant contributors to the CR T values. Among the three metals with high contributions to RQ T , Li and Sr were indispensable trace elements to humans (Liu et al 2018;Schrauzer 2002) and have been widely detected in groundwater worldwide (Duggal et al 2017;Edet et al 2004;Giri and Singh 2015;Golubkina et al 2018;Iqbal and Shah 2012;Kavanagh et al 2017;Kent and Landon 2016;Purushotham et al 2017;Qi et al 2019;Toccalino et al 2012;Voutchkova et al 2018). Previous studies have indicated that the levels of Li or Sr in groundwater were not associated with noncarcinogenic risks (Duggal et al 2017;Edet et al 2004;Giri and Singh 2015;H Zhang et al 2018).…”
Section: Health Risks Of Metalsmentioning
confidence: 99%
“…Under these conditions, Se is predominantly present in the form of labile selenate [20]. High nitrate concentrations are known to create weak oxidation conditions that inhibit microbial Se fixation, which can also cause increased Se concentrations in water [21]. The differences in selenium content between raw and drinking water in individual months were statistically insignificant (p < 0.05) except in June, July, August, and October.…”
Section: Analysis Of Selenium In Watermentioning
confidence: 99%